Peran Pemerintah, Modal Sosial, dan Kinerja Usaha Terhadap Kesejahteraan Subjektif Pelaku Industri Tenun di Kabupaten Jembrana, Bali - Gandhiadi, G.K.; Dharmawan, Komang; Kencana, I Putu Eka Nila (Jurnal Matematika, 2018)
Weaving industry is one of the creative industries based on local wisdom of Bali, need to be developed with the concept of modern entrepreneurship (orange economy). Regional economic development strategies need to take into account the dynamics of local community life or social capital in addition to the role of government and other physical capital, in order to improve the performance of weaving industry in Jembrana regency, Bali. Based on empirical theory and facts, this study aims to analyze how the direct and indirect influence of the role of government, social capital and business performance on and subjective wellbeing on the business actors of weaving industry in Jembrana, Bali. Through the modeling of the resulting structural equations is studied: (1) the direct influence of the government's role on business performance and subjective well-being; (2) the direct influence of social capital on business performance and subjective wellbeing; (3) the direct impact of business performance on subjective well-being; (4) the indirect and total influence of the government's role on subordinate welfare mediated by business performance; and (5) the indirect and total social capital influences on subjective well-being mediated by business performance. Based on surveys and structured interviews on 70 business actors of weaving industry in Jembrana District, Bali through data analysis techniques using SEM-PLS with the help of Smart PLS 3.0 software, in the business actors weaving industry found that: (1) directly the role of government have positive and significant (2) direct social capital has a positive and significant effect on business performance, but not significant to subjective wellbeing, (3) directly the business performance have a positive and significant effect on subjective wellbeing, (4) the role of the government indirectly has a positive but insignificant effect on subjective wellbeing, but through full mediation of business performance, the role of the government has a positive and significant effect on subjective wellbeing, and (5) social capital indirectly has a positive and significant effect on the subjective achievement, so totally through the full mediation of business performance, social capital has a positive and significant impact on subjective wellbeing although it directly does not have a significant effect.